Perspective Plan of Gujarat 1974-1984 Volume I Government of Gujarat General Administration Department (Planning) - Planning Commission (Planning Commission, 1972)
The basic objectives of planned economic development in India must be necessarily guided by the Directive Principles of the Constitution which enjoin the State “to promote the welfare of the people by securing and protecting, as effectively as it may, a social order in which justice, social, economic and political, shall inform all the institutions of national life. The Constitution also directs that all the citizens should have “the right to an adequate means of livelihood”, “that the ownership and control of the material resources of the community are so distributed as best to subserve the common good”, and “that the operation of the economic system docs not result in the concentration of wealth and means of production to the common detriment.
Government of Gujarat General Administration Department (Planning)